Implementation of Cross-Culture Based Instruction in Teaching Listening Comprehension at Indonesian Islamic Higher Education - Nursidah, Nursidah; Ilyas, Ilyas (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
In the context of globalization, cross-cultural competence has become essential, particularly in language learning. Listening comprehension is a vital skill for effective communication, yet many educators overlook its significance, often focusing more on grammar and vocabulary. Despite this, integrating cross-cultural elements in language instruction has been shown to enhance students' communicative abilities. However, there remains a gap in the literature concerning the effective implementation of cross-cultural instruction in listening comprehension, particularly in Islamic higher education in Indonesia. This study aims to explore the implementation of cross-culture-based instruction in teaching listening at Indonesian Islamic Higher Education institutions. A qualitative case study approach was employed, involving two lecturers and 34 students from the English Education Department at State Islamic Institute (IAIN) Bone. Data were collected through classroom observations, questionnaires, and structured interviews. The findings reveal that lecturers utilized a combination of textbook and authentic materials, including YouTube videos and articles, to provide culturally diverse content. Digital tools such as WhatsApp, Google Classroom, and Zoom were also employed, particularly during the COVID-19 pandemic, to facilitate learning. The integration of these tools allowed for flexible instruction, yet the study found limitations in fostering deep cultural understanding through asynchronous communication. In conclusion, while the implementation of cross-culture-based instruction in listening comprehension demonstrated potential, the study highlights the need for a more robust pedagogical framework that fully integrates cultural content with technology. Future research should explore more dynamic methods of engaging students in real-time cultural exchanges to enhance both linguistic proficiency and cross-cultural competence.